Pelestarian Lingkungan: Sinergi Hukum Positif dan Fiqih Ekologi dalam Menjamin Maqasid Syari’ah - Qodri Arrohman; Dian Pertiwi (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2025)
Environmental damage has now reached an alarming level, with Indonesia ranked 10th as the dirtiest country in the world in 2025 based on indicators of air quality, water, waste management, and environmental cleanliness. This study aims to examine the urgency of environmental preservation through the integration of Indonesian positive law, namely Law No. 32 of 2009, with an Islamic legal perspective through the Maqasid Syari'ah approach and the principles of ecological fiqh. The method used is normative juridical with a literature study that examines secondary data in the form of legal and religious literature. The results of the study indicate that environmental preservation is a manifestation of human responsibility as caliphs on earth as mandated in QS. Al-Baqarah verse 30. In the perspective of Maqasid Syari’ah, protecting the environment directly contributes to the protection of five basic elements (al-daruriyat al-khamsah): soul (hifz al-nafs), reason (hifz al-’aql), descendants (hifz al-nasl), wealth (hifz al-mal), and religion (hifz al-din). The strength of this research lies in its ability to directly integrate positive legal aspects with operational theological arguments. The implementation of fiqh principles such as Sadd al-Dzari’ah (preventing permissible acts that lead to damage) and Adh-Dhararu Yuzal (eliminating harm) becomes a strong theological foundation to strengthen the implementation of the law. This research concludes that collective awareness is needed from the Muslim community to practice religious values ​​in preserving nature to ensure the survival of future generations and maintain the objectives of sharia.